Rasch Model Analysis of the Social Prejudice Scale - Fitria, Nita; Faizal, Nur; Irawan, Edy; Nurdin, Astoni; Rosidah, Ainur (Universitas Muria Kudus, 2022)
The measurement of social prejudice requires valid and reliable instruments to produce objective data. Tests of validity and reliability with classical theory on the instrument were found to have many weaknesses that required in-depth analysis so that the data obtained were not biased. This study aims to analyze the social prejudice scale of students by using the Rasch model approach. 50 respondents were taken from students of Guidance and Counseling study program. The numbers of items on the scale of social prejudice were 25 items. Data was analyzed using WinstepS software. The method used in this analysis was Rasch modeling method. Based on the analysis of 25 statements developed, there were 23 items that meet the standards that while the other items did not meet the standards. The reliability value of the scale is 0.86 which means that it is in a good category. The overall scale of social prejudice developed can be used to measure a student’s level of social prejudice.